Sekurytyzacja w polskim prawie - kluczowe regulacje prawne - Kalasińska, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In Poland lack of proper legal regulation-related to securitization, which would facilitate adaptation of this method on polish market, in bank sector particularly. Consciousness of such condition caused that legislator has taken activities to input to polish legal system of certain legislative solution concerning securitization. Part of this regulations have already found in obligatory polish law. The major regulations related to securitization, legislator has included in bank law and in investment funds act. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 151-155